THE INFLUENCE OF PROFIT AND CASH FLOW TO PREDICT FINANCIAL DISTRESS - Sinambela, Tongam; Marpaung, Agus Irawati (Dinasti International Journal of Management Science, 2019)
This study aims to examine and analyze how profit and cash flow individually or collectively could influence the prediction of financial distress. This study uses quantitative data methods using the Altman Z-Score analysis method. Data analysis is performed through Eviews8 software application. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the period from 2015-2018. The samples used are all manufacturing companies with subsector of plastic and packaging. Data analysis in this study uses econometric model with a simultaneous equation system and data panel estimation method. The results of the study prove that profit does not have a significant effect on financial distress. This is supported by t-test analysis which result in a smaller t-count compared to t-table, with the number -1.76 <2.05, therefore, H1 is rejected. On the other hand, cash flow has a significant effect on financial distress, supported by the result of t-test analysis which shows that the t-count is bigger than t-table, with the number 2.67> 2.05. Therefore, H2 is accepted. Whereas, both profit and cash flow have a significant influence on financial distress, which the results of the analysis of the F test is f-count is higher that f-table, with the number 17.45> 170.77. As a result, H3 is accepted